Plastic containing fat powder
By blending specific oils and oil powders with plastics, the environmental impact of petroleum-based plastics is reduced, and biodegradable alternatives with increased haze are created, addressing the need for sustainable and functional plastics.
Patent Information
- Application Number
- JP2024157109
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-03-26
- Filing Date
- 2024-09-11
- Publication Date
- 2025-04-14
Smart Images

Figure 2025062571000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a fat powder-blended plastic. [Background technology]
[0002] Polypropylene, low-density polyethylene, and high-density polyethylene are widely used in modern industrial fields, but because they are produced from petroleum-based raw materials, they pose a problem of environmental burden. In recent years, the movement to be environmentally conscious and pursue sustainability has been expanding, and there is a demand for alternative raw materials, etc. In this context, the development of environmentally friendly products that reduce the proportion of petroleum-based raw materials by adding plant-based raw materials to the ingredients has been attracting attention. Plant raw materials are renewable resources and are abundant on earth. They are also considered to have a lower environmental impact than petroleum-based raw materials. Therefore, the use of plant raw materials in the production of various resins can be an important tool for sustainable development. In view of these circumstances, various materials have been developed, such as a resin composition in which a thermoplastic resin is blended with a wood-based material (see Patent Document 1), a bioplastic made by mixing a wood-based material, a resin material, and an impact resistance improver (see Patent Document 2), and a molding resin material containing a roasted wood-based biomass or a pulverized wood-based biomass carbonized material having an average particle size of 100 μm or less, and further containing a polyamide-based resin (see Patent Document 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 10-330624 [Patent Document 2] JP 2009-113375 A [Patent Document 3] JP 2023-83053 A Summary of the Invention [Problem to be solved by the invention]
[0004] An object of the present invention is to provide an environmentally friendly plastic by blending plant-derived raw materials into the plastic, thereby reducing the proportion of petroleum-based raw materials used. Another object of the present invention is to provide a plastic having an increased degree of haze, which is a plant-derived biodegradable plastic made from starch as a raw material. [Means for solving the problem]
[0005] As a result of extensive research to solve the above problems, the inventors discovered that by blending a specific oil powder into a plastic, the proportion of petroleum-based raw materials used can be reduced and the degree of haze of polylactic acid can be increased, thereby completing the present invention.
[0006] That is, the present invention relates to the following. [1] A plastic containing oil powder, characterized in that the plastic contains oil powder having an average particle size of 50 μm or less and a melting point of 55° C. or more. [2] The oil powder-blended plastic according to [1], wherein the plastic is selected from polypropylene, low-density polyethylene, high-density polyethylene, and polylactic acid. [3] The oil / fat powder blended plastic according to [1] or [2], wherein the blending amount of the oil / fat powder is 0.1 to 35 mass%. [4] The oil / fat powder-blended plastic according to any one of [1] to [3], characterized in that the oil / fat powder-blended plastic has a haze. [5] The oil / fat powder-blended plastic according to any one of [1] to [4], characterized in that the oil / fat powder-blended plastic is in the form of a sheet. [6] A method for producing a sheet-shaped oil-and-fat powder-blended plastic, comprising kneading a plastic with an oil and fat powder having an average particle size of 50 μm or less and a melting point of 55° C. or more, and heating and melting and pressurizing the resulting kneaded product. [7] A method for producing a sheet-shaped oil-and-fat powder-blended plastic according to [6], characterized in that the obtained kneaded product is cut and then pressurized and heated. [8] The method for producing a sheet-shaped oil-and-fat powder-blended plastic according to [6] or [7], wherein the plastic is selected from polypropylene, low-density polyethylene, high-density polyethylene, and polylactic acid. [9] A clouding agent for plastics, comprising a fat or oil powder having an average particle size of 50 μm or less and a melting point of 55° C. or more, and capable of clouding plastics.
[10] A friction enhancer for plastic surfaces, which comprises a fat powder having an average particle size of 50 μm or less and a melting point of 55° C. or higher, and which improves the friction of plastic surfaces. Effect of the Invention
[0007] According to the present invention, an environmentally friendly plastic can be obtained by reducing the proportion of petroleum-based raw materials used, and therefore an environmentally friendly plastic can be provided. Furthermore, according to the present invention, it is possible to provide a plastic having an increased degree of haze of polylactic acid, which is a plant-derived biodegradable plastic made from starch, and therefore the plastic of the present invention can be used particularly in applications where it is desired to prevent the view through the plastic. Furthermore, even when a specific oil or fat powder is blended with a plastic derived from a petroleum-based material or a plant, bleeding is unlikely to occur. Therefore, it has been found that the plastic of the present invention may be usable in applications where bleeding is undesirable. [Brief description of the drawings]
[0008] [Figure 1] 1 is a photograph showing the degree of cloudiness of a plastic sheet made from polylactic acid in Reference Example 4. [Diagram 2] 1 is a photograph showing the degree of cloudiness of a plastic sheet (containing 10% by mass of oil powder) made from the polylactic acid of Example 6. [Diagram 3]1 is a photograph showing the degree of cloudiness of a plastic sheet (containing 10% by mass of canola oil (2)) made from polylactic acid in Reference Example 4. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Specific embodiments of the present invention will be described in detail below. However, the present invention is not limited to the following embodiments, and can be implemented with appropriate modifications within the scope of the object of the present invention.
[0010] The present invention is an oil powder-blended plastic in which an oil powder having an average particle size of 50 μm or less and a melting point of 55° C. or more is blended with a plastic. The present invention also provides a method for producing a sheet-shaped oil-and-fat powder-blended plastic, which comprises kneading a plastic with an oil-and-fat powder having an average particle size of 50 μm or less and a melting point of 55° C. or more, and then heating, melting, and pressurizing the resulting kneaded product. The present invention also relates to a clouding agent for plastics, which comprises a fat or oil powder having an average particle size of 50 μm or less and a melting point of 55° C. or more, and is capable of clouding plastics.
[0011] 〔plastic〕 The petroleum-based plastic used in the present invention is preferably a thermoplastic resin, and polyolefin resins such as polypropylene, polyethylene, and ethylene-vinyl acetate copolymers are preferred, as they are highly versatile, have relatively low molding temperatures, and are inexpensively available. Moreover, polylactic acid can be used as a plant-derived plastic.
[0012] Polypropylene (hereinafter sometimes abbreviated as PP) is a synthetic resin produced from propylene, which is obtained by cracking and refining naphtha (crude gasoline), a fraction of crude oil. It is lightweight and heat-resistant, and is widely used for product packaging. There are two types of polyethylene: low-density polyethylene (hereinafter sometimes abbreviated as LDPE) and high-density polyethylene (hereinafter sometimes abbreviated as HDPE). Low-density polyethylene is polyethylene with a density of less than 0.910 to 0.930, and is produced by polymerizing ethylene obtained by thermal cracking of naphtha, an intermediate product made from petroleum, under high pressure of around 2000 atmospheres. High density polyethylene has a density of 0.942 to 0.970 and is characterized by being harder and more rigid than low density polyethylene. High density polyethylene is produced by polymerizing ethylene obtained by thermal cracking of naphtha, a petroleum-based raw material, under pressure ranging from normal pressure to several atmospheres. Also, ethylene vinyl acetate (EVA) is produced by copolymerizing ethylene and vinyl acetate monomers. In addition, polylactic acid (hereinafter sometimes abbreviated as PLA) is a plant-derived, biodegradable plastic made from starch contained in corn and other crops, and since it does not increase carbon dioxide in the atmosphere even when incinerated (it is carbon neutral), it has a lower environmental impact than petroleum-derived plastics.
[0013] [Oil powder] First, the oil or fat powder used in the present invention will be described. Examples of raw materials for the oil and fat powder of the present invention include palm stearin, extremely hardened palm oil, extremely hardened rapeseed oil, extremely hardened high erucic acid rapeseed oil, extremely hardened soybean oil, extremely hardened sunflower oil, extremely hardened safflower oil, etc., in which 80 mass % or more of the fatty acids constituting the oil and fat are saturated fatty acids having 16 or more carbon atoms, and one or more of these can be used. The melting point of the oil or fat powder is 55°C or higher, preferably 58°C or higher, and more preferably 61°C or higher, and the upper limit of the melting point is preferably 90°C or lower, more preferably 80°C or lower, and even more preferably 75°C or lower. The oil powder of the present invention is different from powdered oil obtained by spray-drying an emulsion of an aqueous solution containing oil, excipients, emulsifiers, etc.
[0014] The melting point of the oil powder used in the present invention can be determined by DSC (differential scanning calorimeter) measurement, for example, a sample was heated at a temperature increase rate of 10°C / min using a DSC (DSC1 manufactured by Mettler Toledo) to measure the endothermic curve. The melting point can be determined as the temperature at the intersection of the baseline before the start of endothermic reaction by heating and the descending line of the endothermic peak.
[0015] The average particle size (effective diameter) of the oil or fat powder used in the present invention is 50 μm or less, preferably 0.5 to 50 μm, more preferably 0.5 to 40 μm, even more preferably 1 to 30 μm, and most preferably 1 to 20 μm. Here, the average particle size (effective diameter) refers to the volume average diameter [MV], and the volume average diameter [MV] is obtained by measuring the volume-based particle size distribution by dry measurement using a particle size distribution measuring device (e.g., Shimadzu Corporation, device name: SALD-2300) based on the laser diffraction scattering method (ISO13320, JIS Z 8825-1), and the obtained volume average diameter [MV] is the average particle size. The volume average diameter [MV] can be calculated from the following formula using the particle size, particle volume, and the sum of the particle volumes. Volume mean diameter [MV] = sum of (particle diameter x volume of the particle) / sum of particle volumes The effective diameter means the particle diameter of the sphere when the measured diffraction pattern of the crystal to be measured matches the theoretical diffraction pattern obtained assuming the crystal to be spherical. In this way, in the case of the laser diffraction scattering method, the effective diameter is calculated by matching the theoretical diffraction pattern obtained assuming the crystal to be spherical with the measured diffraction pattern, so that the measurement can be performed under the same principle whether the measurement object is plate-shaped or spherical.
[0016] The method for producing the oil and fat powder used in the present invention is not particularly limited. For example, the oil and fat powder raw material having a melting point of 55° C. or higher can be produced by pulverizing the oil and fat powder raw material using a pulverizer such as a cyclone mill or a hammer mill, airflow pulverization using a fluidized bed jet mill or a counter type jet mill, freeze pulverization, extrusion granulation, spray cooling, or other conventionally known method.
[0017] The fat and oil powder used in the present invention contains a fat and oil component. The fat and oil component contains at least a XXX type triglyceride and optionally contains other triglycerides. The oil and fat component contains one or more XXX type triglycerides having fatty acid residues X with carbon number x at positions 1 to 3 of glycerin. The XXX type triglycerides are triglycerides having fatty acid residues X with carbon number x at positions 1 to 3 of glycerin, and each fatty acid residue X is the same as each other. Here, the carbon number x is an integer selected from 16 to 20, preferably an integer selected from 16 to 18, and more preferably 18. The fatty acid residue X may be a saturated or unsaturated fatty acid residue. Specific examples of the fatty acid residue X include, but are not limited to, palmitic acid, stearic acid, and arachidic acid. More preferred fatty acids are palmitic acid and stearic acid, and even more preferred is stearic acid. The content of the XXX triglyceride is, for example, 50% by mass or more, preferably 60% by mass or more, more preferably 70% by mass or more, and even more preferably 80% by mass or more, with the lower limit being, for example, 100% by mass or less, preferably 99% by mass or less, and more preferably 95% by mass or less, when the total mass of the oil powder or oil component is taken as 100% by mass. One or more types of XXX triglyceride can be used, preferably one or two types, and more preferably one type is used. When two or more types of XXX triglyceride are used, the total value is the content of the XXX triglyceride.
[0018] The fat and oil component may contain other triglycerides other than the above-mentioned XXX triglyceride, so long as the effect of the present invention is not impaired. The other triglycerides may be a plurality of types of triglycerides, and may be synthetic fats and oils or natural fats and oils. Examples of synthetic fats and oils include glyceryl tricaprylate and glyceryl tricaprate. Examples of natural fats and oils include cocoa butter, sunflower oil, rapeseed oil, soybean oil, cottonseed oil, and the like. When the total triglycerides in the fat and oil powder or the fat and oil component are taken as 100% by mass, there is no problem even if the other triglycerides are contained in an amount of, for example, 1% by mass or more, or about 5 to 50% by mass, when the total mass of the fat and oil powder or the fat and oil component is taken as 100% by mass. The content of other triglycerides is, for example, 0 to 50 mass%, preferably 5 to 40 mass%, more preferably 10 to 30 mass%, and even more preferably 15 to 25 mass%, when the total mass of the oil and fat powder or the oil and fat component is 100 mass%.
[0019] The fat and oil powder preferably consists essentially of the fat and oil component, and the fat and oil component preferably consists essentially of triglycerides. Moreover, "substantially" means that the components other than the fat and oil component contained in the fat and oil powder or the components other than triglycerides contained in the fat and oil component are, for example, 0 to 15% by mass, preferably 1 to 10% by mass, and more preferably 2 to 5% by mass, when the fat and oil powder or the fat and oil component is taken as 100% by mass.
[0020] The content of the oil and fat powder in the oil and fat powder blended plastic is preferably 0.005 to 35 mass%, more preferably 0.05 to 35 mass%, even more preferably 0.1 to 35 mass%, even more preferably 1 to 35 mass%, particularly preferably 1 to 30 mass%, and most preferably 1 to 15 mass%.
[0021] [Other additives] To the oil / fat powder-blended plastic of the present invention, a release agent such as lecithin, inorganic materials such as titanium dioxide, talc, calcium carbonate, organic materials such as carbon black, antioxidants, plasticizers, light stabilizers, ultraviolet absorbers, antibacterial agents, etc. can be added. The content of these other additives in the oil / fat powder blended plastic is preferably 0.01 to 10 mass %, and more preferably 0.05 to 5 mass %.
[0022] [Molded product] The oil / fat powder-blended plastic of the present invention can be molded for various purposes and can also be made into a sheet shape. Examples of molded articles obtainable using the oil / fat powder-blended plastic of the present invention include containers, cups, trays, toys, packaging materials, and the like.
[0023] [Method for producing plastic containing oil and fat powder] Next, a method for producing the plastic containing oil and fat powder will be described. The fat / oil powder-blended plastic of the present invention can be produced, for example, by kneading the fat / oil powder into a plastic and heating the mixture. Specifically, plastics such as polypropylene, low-density polyethylene, high-density polyethylene, polylactic acid, etc. and oil and fat powder are fed into a kneader, kneaded at a temperature 2 to 30°C higher than the melting temperature of the plastic for 1 minute to 1 hour, and the resulting kneaded product is molded at a temperature 2 to 30°C higher than the melting temperature of the plastic. For example, when molding into a sheet, the obtained kneaded material is cut into pieces having a maximum length of about 2 cm or less as necessary, and the cut kneaded material is heated, melted, and pressed using a heat press to produce a powdered oil-blended plastic sheet. The heating and melting temperature during pressing is preferably 2 to 30°C higher than the melting temperature of the plastic, the heating and melting time during pressing is preferably 1 to 30 minutes, the pressing pressure is preferably 1 to 20 tons, and the pressing time is preferably 10 seconds to 10 minutes.
[0024] [Friction improver for plastic surfaces] Fat powder with an average particle size of 50 μm or less and a melting point of 55° C. or more can improve (optimize) the frictional force of the plastic surface by blending it with plastic. Therefore, fat powder with an average particle size of 50 μm or less and a melting point of 55° C. or more can be used as a frictional force improver for plastic surfaces. Note that improving the frictional force includes both cases where the frictional force of the plastic surface is increased by raising the frictional force, and where the frictional force of the plastic surface is increased by lowering the frictional force. For this reason, the present invention makes it possible to produce non-slip plastics, which can be used for, for example, stationery such as non-slip pens, non-slip rulers, and non-slip scissors, as well as non-slip containers. Furthermore, since the frictional force of the plastic surface is improved, when writing characters or the like on the plastic with a pen such as a magic marker, the writing feel and ease of the pen can be improved. The coefficient of friction of the surface of a plastic sheet can be measured using a device capable of measuring the coefficient of friction of an object. For example, by using a measuring device "KES-SE Friction Feeling Tester" manufactured by Kato Tech Co., Ltd., it is possible to measure the difference in frictional force that is close to the feeling when touching with a finger. EXAMPLES
[0025] The present invention will now be described in detail with reference to examples, but the present invention is not limited to these examples.
[0026] [Raw materials used in the manufacture of plastic sheets] The raw materials used in the production of the plastic sheets are shown in Table 1.
[0027] [Table 1]
[0028] Here, the oil powder is an oil powder sold by Nisshin Oillio Group Ltd. (product name "KonaFat #2"), which has an average particle size of 10.0 μm, a melting point of 68.2°C, and a content of XXX type triglyceride having a fatty acid residue X (stearic acid residue) with 18 carbon atoms at the 1st to 3rd positions of glycerin of 79.6% by mass when the total mass of the oil powder is taken as 100% by mass. Conafat #2 is a white oil powder made from edible oils and fats derived from plants.
[0029] The analytical method for oil and fat powder is described below. Average particle size of oil powder The average particle size was determined by measuring the volumetric particle size distribution by dry measurement using a particle size distribution analyzer (Shimadzu Corporation, device name: SALD-2300) based on the laser diffraction scattering method (ISO13320, JIS Z 8825-1) to obtain the volume average diameter [MV], which was then used as the average particle size. The volume average diameter [MV] was calculated from the following formula using the particle size, particle volume, and the sum of the particle volumes. Volume mean diameter [MV] = sum of (particle diameter x volume of the particle) / sum of particle volumes Melting point of oil powder Using a DSC (Mettler Toledo DSC1), the sample was heated at a rate of 10°C / min to measure the endothermic curve. The melting point was determined as the temperature at the intersection of the baseline before the endothermic peak began and the descending line of the endothermic peak. Triglyceride composition The triglyceride composition was analyzed by gas chromatography under the following gas chromatography analysis conditions. DB1-ht (0.32mm x 0.1μm x 5m) Agilent Technologies (123-1131) Injection volume: 1.0μL Inlet: 370℃ Detector: 370℃ Split ratio: 50 / 1 35.1kPa constant pressure Column CT: 200℃(0min hold)~(15℃ / min)~370℃(4min hold)
[0030] [Production of Plastic Sheets (Using Polypropylene) (Examples 1 to 3, Reference Examples 1 to 3)] Polypropylene (mixture amount 95 mass% (Example 1), 90 mass% (Example 2), 70 mass% (Example 3)) and oil powder (mixture amount 5 mass% (Example 1), 10 mass% (Example 2), 30 mass% (Example 3)) were put into a kneader (apparatus name "Labo Plastomill 4C150", mixing unit "Banbury Mixer B75", manufactured by Toyo Seiki Seisakusho), and kneaded under the following kneading conditions. The obtained kneaded product was cut into a size with a maximum length of about 2 cm or less. The cut kneaded product was heated, melted and pressed using a heat press machine (apparatus name "AH-2003", manufactured by AS ONE) under the following pressing conditions to produce a powdered oil-blended plastic sheet (Examples 1 to 3). Mixing conditions: 195℃, 100 rpm, shear mixing for 5 minutes Press conditions: Melt the mixture at 195℃ for 5 minutes, then press mold at the same temperature for 1 minute at 5 tons In addition, the oil and fat powders of Examples 1 to 3 were replaced with canola oil (1) (blending amount: 5 mass% (Reference Example 1), 10 mass% (Reference Example 2), 30 mass% (Reference Example 3)), and plastic sheets were produced in the same manner as in Examples 1 to 3 (Reference Examples 1 to 3). Furthermore, as a confirmation experiment, a plastic sheet was produced in the same manner as in Example 1, without blending the oil and fat powder of Example 1 (using only polypropylene), and the plastic sheet could be produced without any problems.
[0031] [Production of plastic sheet (using low density polyethylene) (Example 4, Comparative Examples 1 and 2)] Low-density polyethylene (90% by mass blending amount) and oil powder (10% by mass blending amount) were fed into a kneader (Labo Plastomill 4C150, mixing unit Banbury Mixer B75, manufactured by Toyo Seiki Seisakusho) and kneaded under the following kneading conditions. The resulting kneaded product was cut into pieces with a maximum length of approximately 2 cm or less. The cut kneaded product was heated, melted and pressed using a heat press machine (AH-2003, manufactured by AS ONE) under the following pressing conditions to produce a powdered oil-blended plastic sheet (Example 4). Mixing conditions: 135℃, 100 rpm, shear mixing for 5 minutes Press conditions: Melt the mixture at 150℃ for 5 minutes, then press mold at the same temperature for 1 minute at 5 tons Moreover, a plastic sheet was produced in the same manner as in Example 4, except that the oil and fat powder in Example 4 was replaced with canola oil (1) (blended amount: 10 mass %) (Comparative Example 1). Moreover, a plastic sheet was produced in the same manner as in Example 4, except that the oil and fat powder in Example 4 was replaced with palm oil (blended amount: 10 mass %) (Comparative Example 2). Also, as a confirmation experiment, a plastic sheet was produced in the same manner as in Example 4, but without blending the oil powder of Example 4 (using only low-density polyethylene), and the plastic sheet could be produced without any problems.
[0032] [Production of plastic sheet (using high density polyethylene) (Example 5, Comparative Examples 3 and 4)] High-density polyethylene (90% by mass blending amount) and oil powder (10% by mass blending amount) were fed into a kneader (Labo Plastomill 4C150, mixing unit Banbury Mixer B75, manufactured by Toyo Seiki Seisakusho) and kneaded under the following kneading conditions. The resulting kneaded product was cut into pieces with a maximum length of approximately 2 cm or less. The cut kneaded product was heated, melted and pressed using a heat press machine (AH-2003, manufactured by AS ONE) under the following pressing conditions to produce a powdered oil-blended plastic sheet (Example 5). Mixing conditions: 165℃, 100 rpm, shear mixing for 5 minutes Press conditions: Melt the mixture at 175℃ for 5 minutes, then press mold at the same temperature for 1 minute at 5 tons Moreover, a plastic sheet was produced in the same manner as in Example 5, except that the oil and fat powder in Example 5 was replaced with canola oil (1) (blended amount: 10 mass %) (Comparative Example 3). Moreover, a plastic sheet was produced in the same manner as in Example 5, except that the oil and fat powder in Example 5 was replaced with palm oil (blended amount: 10 mass %) (Comparative Example 4). Also, as a confirmation experiment, a plastic sheet was produced in the same manner as in Example 5, without blending the oil powder of Example 5 (using only high density polyethylene), and the plastic sheet could be produced without any problems.
[0033] [Production of plastic sheet (using polylactic acid) (Example 6, Comparative Example 5)] Polylactic acid (mixture amount 90% by mass) and oil powder (mixture amount 10% by mass) were put into a kneader (apparatus name "Plasticoda Labo Station", mixing unit "W50EHT" manufactured by Plavender) and kneaded under the following kneading conditions. The kneaded product obtained was cut into pieces with a maximum length of approximately 2 cm or less. The cut kneaded product was heated, melted and pressed using a heat press machine (apparatus name "IMC-1AE4" manufactured by Imoto Machinery Co., Ltd.) under the following pressing conditions to produce a powdered oil-blended plastic sheet (Example 6). Kneading conditions: 180℃, 50rpm, 5 minutes Pressing conditions: Melt the mixture at 180℃, and apply a deformation pressure of 6MPa at the same temperature. Moreover, a plastic sheet was produced in the same manner as in Example 6, except that the oil and fat powder in Example 6 was replaced with canola oil (2) (blended amount: 10 mass %) (Comparative Example 5). In addition, a plastic sheet was produced in the same manner as in Example 6, without blending the oil and fat powder in Example 6 (only polylactic acid), and the plastic sheet could be produced without any problems (Reference Example 4).
[0034] [Evaluation results of plastic sheets] The obtained plastic sheets were subjected to the following evaluations, and the results are shown in Tables 3 to 7. Breed Rating The presence or absence of bleeding was visually observed immediately after kneading in the production of the plastic sheet, and after pressing. Also, the presence or absence of bleeding was visually observed one day after pressing. The term "bleeding" refers to the seeping out of liquid or solid from the surface of the resin. Immediately after mixing The state immediately after kneading was visually observed. - Cloudiness of plastic sheet (evaluated only for transparent polylactic acid) The degree of haze of the resulting plastic sheet using polylactic acid was evaluated. Specifically, a paper container with colored letters and pictures (pictures of vegetables) was placed 3 cm behind the plastic sheet, and the visibility of the letters and pictures was observed, and the degree of cloudiness was evaluated based on the evaluation criteria in Table 2.
[0035] [Table 2]
[0036] [Table 3]
[0037] [Table 4]
[0038] [Table 5]
[0039] [Table 6]
[0040] [Table 7]
[0041] The results in Tables 3 to 7 reveal the following: It was found that by blending plant-derived oil powder with petroleum-based polypropylene, low-density polyethylene, and high-density polyethylene, bleeding did not occur one day after pressing. On the other hand, when canola oil was used instead of oil powder, a plastic sheet that did not bleed could be produced with polypropylene, but bleeding occurred one day after pressing with low-density polyethylene and high-density polyethylene. In addition, when palm oil was used instead of oil powder, bleeding occurred one day after pressing with low-density polyethylene and high-density polyethylene. This demonstrated that the use of oil and fat powder may enable the production of environmentally friendly plastics that use a reduced proportion of petroleum-based raw materials. They also found that by blending plant-derived oil powder with polylactic acid, a plant-derived biodegradable plastic, they could produce a plastic sheet that did not bleed after one day of pressing. Furthermore, by blending the oil powder, they were able to obtain a plastic with a higher degree of haze than when canola oil was blended.
[0042] [Production of plastic sheets (using low density polyethylene) (Reference Example 5, Examples 7 and 8)] Low-density polyethylene (99.9% by mass) and oil powder (0.1% by mass) were fed into a kneader (Labo Plastomill 4C150, mixing unit Banbury Mixer B75, manufactured by Toyo Seiki Seisakusho) and kneaded under the following kneading conditions. The resulting kneaded product was cut into pieces with a maximum length of approximately 2 cm or less. The cut kneaded product was heated, melted and pressed using a heat press machine (AH-2003, manufactured by AS ONE) under the following pressing conditions to produce a powdered oil-blended plastic sheet (Example 7). Mixing conditions: 135℃, 100 rpm, shear mixing for 5 minutes Press conditions: Melt the mixture at 150℃ for 5 minutes, then press mold at the same temperature for 1 minute at 5 tons In addition, a powdered oil-blended plastic sheet was produced in the same manner as in Example 5, except that the blending amount of low-density polyethylene was 99.5 mass % and the blending amount of oil powder was 0.5 mass % (Example 8). As a comparative experiment, a plastic sheet was produced in the same manner as in Example 5, but without blending the oil powder of Example 5 (using only low-density polyethylene), and the plastic sheet could be produced without any problems.
[0043] [Measurement of the coefficient of friction of the surface of a plastic sheet] The friction coefficient of the surface of the plastic sheets of Reference Example 5, Examples 7, and 8 was measured using a measuring device "KES-SE Friction Feeling Tester" manufactured by Kato Tech Co., Ltd., under the following conditions that allow the difference in frictional force to be measured similar to the feeling of touching with a finger. The feeling of touching the surface of the plastic sheet when stroked with a finger was also examined. The results are shown in Table 8. [Measurement conditions] Static load 50g, speed 1mm / sec, 10mm square piano wire sensor
[0044] [Table 8]
[0045] The results in Table 8 reveal the following: It has been discovered that by blending plant-derived oil powder with low-density polyethylene made from petroleum-based raw materials, it is possible to produce a plastic sheet with improved friction on the plastic surface. For this reason, the present invention makes it possible to produce non-slip plastics, which can be used for, for example, non-slip pens, rulers, scissors, and other stationery and containers.
Claims
1. A plastic containing oil and fat powder, the plastic being characterized in that the plastic is compounded with oil and fat powder having an average particle size of 50 μm or less and a melting point of 55° C. or more.
2. The oil and fat powder blended plastic according to claim 1, wherein the plastic is selected from the group consisting of polypropylene, low density polyethylene, high density polyethylene, and polylactic acid.
3. The oil / fat powder blended plastic according to claim 1, wherein the blending amount of the oil / fat powder is 0.1 to 35 mass%.
4. 2. The oil / fat powder-blended plastic according to claim 1, characterized in that the oil / fat powder-blended plastic has a haze.
5. The oil / fat powder blended plastic according to any one of claims 1 to 4, characterized in that the oil / fat powder blended plastic is in the form of a sheet.
6. A method for producing a sheet-shaped oil-and-fat powder-containing plastic, comprising kneading a plastic with an oil and fat powder having an average particle size of 50 μm or less and a melting point of 55° C. or more, and then heating and melting and pressurizing the resulting kneaded product.
7. 7. The method for producing a sheet-shaped oil and fat powder-containing plastic according to claim 6, wherein the obtained kneaded product is cut and then pressurized and heated.
8. The method for producing a sheet-shaped oil and fat powder-blended plastic according to claim 6 or 7, wherein the plastic is selected from the group consisting of polypropylene, low-density polyethylene, high-density polyethylene, and polylactic acid.
9. A fogging agent for plastics, which comprises a fat powder having an average particle size of 50 μm or less and a melting point of 55° C. or more, and is capable of fogging plastics.
10. A friction enhancer for plastic surfaces, which comprises a powdered oil or fat having an average particle size of 50 μm or less and a melting point of 55° C. or more, and which enhances the friction of plastic surfaces.
Citation Information
Patent Citations
Bioplastic and bioplastic molded article
JP2009113375A
Resin material for molding
JP2023083053A
JP330624A